Answer: $216
Step-by-step explanation:
Hope it helped
Answer: M =
Step-by-step explanation:
![\frac{M(x+y)+4y}{x^{2}-xy-y^{2} } =\frac{(x+2y)}{x^{2} -xy-y^{2} }](https://tex.z-dn.net/?f=%5Cfrac%7BM%28x%2By%29%2B4y%7D%7Bx%5E%7B2%7D-xy-y%5E%7B2%7D%20%20%7D%20%3D%5Cfrac%7B%28x%2B2y%29%7D%7Bx%5E%7B2%7D%20-xy-y%5E%7B2%7D%20%7D)
M (x + y) + 4y = x + 2y (Multiply
in both sides)
M (x + y) = x + 2y - 4y
M (x + y) = x - 2y (Divide (x+y) from both sides)
M =
Answer:
I believe the answer is B.
Step-by-step explanation: